Pengaruh Penambahan Unsur Titanium-Boron (Ti-B) 0,1% dan 0,5% Terhadap Nilai Kekerasan Paduan Alumunium - Wisnujati, Andika; Shomad, M. Abdus (Universitas Muhammadiyah Yogyakarta, 2019)
This study discusses the composition of the material contained in the used piston material and compares the strength value of each variation of Ti-B percentage by violence testing. The method used in metal casting is Gravity Casting which uses only gravity of the earth. In the manufacture of this recycled piston includes several stages of the process of working method with Sand Casting mold and its test. Among them are pattern planning, raw material preparation, pattern making, pasri printing, mold making with CO2 gas, aluminium metal smelting, Ti-B input into melt kitchen, casting of liquid metal, casting specimen and final process. The result of composition testing of main alloy material is 84,19 % Al and 10,8306 % Si. The result of hardness testing with gravity casting method on the percentage of Ti-B 0,1% and 0,5% using sand casting mold have hardness number 52,62 VHN and 71,76 VHN. The percentage of addition of Ti-B element greatly affect the mechanical properties of the material, so that more Ti-B element, then the material will have hard mechanical properties